Legal aspects of planetary defence - Marboe, Irmgard (Studies in space law, 2021)
"Impacts by asteroids or comets on Earth may lead to natural disasters of catastrophic dimensions, the most famous being the extinction of the dinosaurs 66 million years ago. Space agencies and other actors are increasingly active in activities dedicated to the development of technology to predict and mitigate such risks. This book addresses legal and policy aspects of 'planetary defence' activities aiming at the mitigation of Near-Earth Objects (NEO) impact threats. These include responsibility and liability for damage caused by such activities (or their failure) as well as international cooperation and possible decision making processes"--